Lock-in Amplifier as a Sensitive Instrument for Biomedical Measurement : Analysis and Implementation - Yasser Abd Djawad; Janice Kiely; Patrick Wraith; Richard Luxton (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A measuring instrument plays important role in the biomedical measurement since the biological process in living organism generates very weak signal. Therefore, a reliable and sensitive measuring instrument is needed. In this study, a lock-in amplifier was analysed and tested. This paper presents an experiment to investigate the lock-in amplifier for biomedical measurement. An experiment using RC (resistor capacitor) tissue model to measure the voltage change related to impedance change was performed using a lock-in amplifier to evaluate the accuracy of the lock-in amplifier. Three different values of the capacitor in the RC tissue model were applied regarding to simulate small impedance changes. The measurement results were compared with the theoretical calculation and an impedance measurement system. An error analysis was conducted to investigate the accuracy of the measurement. The comparison result showed that impedance measurement using lock-in amplifier is an effective technique, which could able to measure very small voltage regarding impedance change in the RC tissue model.